KOMUNIKASI TRANSENDENTAL DAN EPISTIMOLOGI ISLAM : (PERSEPEKTIF EMPIRIS-METODIS: BURHANI DAN IRFANI) - Nur Ainiyah; Faiz Zainuddin; Hasanah (Fakultas Dakwah Universitas Ibrahimy, 2020)
Empirically transcendental communication creates inner experiences for humans. Humans as communicators convey messages in prayer as a medium of communication against God as an absolute communicator. The effect in transcendental communication felt by humans is inner peace or tranquility of the soul. In Islamic epistemology methodically known methods of thinking bayani, burhani and irfani. Burhani is a framework for thinking that is not based on sacred texts, nor experience. The aim of the viewfinder is exoteric, so the way it works is based on logic wrangling. Burhani is a framework for thinking that is not based on sacred texts, nor experience. The aim of the viewfinder is exoteric, so the way it works is based on logic wrangling. Irfani is a thinking methodology model based on direct experience and approaches to religious spiritual reality. With Burhani's methodical reasoning humans use their minds in analyzing empirical events that are seen, heard and felt. But reason alone is not enough in processing human experience. then with the method of intuition or irfani use the heart to feel the inner experience that humans pass in each event of his life. The union with his Lord in prayer, which is manifested in his prayers, fasting and other worship become part of the process of human transcendental communication